Comparative Analysis of Share Index Movements Due to the Impact of the Covid-19 Pandemic on The JCI and JII Indexes in Indonesia - Lestari, Khofifah Trisnah; Rosyada, Mohammad (Nominal: Barometer Riset Akuntansi dan Manajemen, 2024)
ABSTRACTThe stock index is the primary reference used to show increases and decreases in stock prices and the performance of all stocks on the Indonesia Stock Exchange (IDX). This study aims to determine whether there is a difference between the movement of the JCI and JII indices due to the impact of the Covid-19 pandemic in 2019-2020. This type of research is descriptive with a quantitative approach. The data used in this study is secondary data with a sample of 35 daily data (series) on the closing value of stock transactions on the IDX using the IDX website. The sampling technique used purposive sampling with the Independent Sample T-test analysis method. The results of this study were 1) there were differences between the movements of the JCI and JII before the Covid-19 pandemic, 2) there were differences between the movements of the JCI and JII during the Covid-19 pandemic, 3) there were differences between the movements of the JCI and JII after the new normal. Thus, there is a significant difference between the movement of the JCI and JII due to the impact of the Covid-19 pandemic.Keywords: Stock Investment Decision, Stock Price Index, Stock Price MovementsABSTRAKIndeks saham merupakan acuan utama yang digunakan sebagai parameter untuk menunjukkan kenaikan dan penurunan harga saham serta kinerja semua saham di Bursa Efek Indonesia (BEI). Tujuan dari penelitian ini untuk mengetahui ada atau tidaknya perbedaan antara pergerakan indeks IHSG dan JII akibat dampak pandemic Covid-19 tahun 2019-2020. Jenis penelitian ini adalah deskriptif dengan pendekatan kuantitatif. Data yang digunakan dalam penelitian ini adalah data sekunder dengan sampel sebanyak 35 data harian (series) pada nilai penutupan saham transaksi saham di BEI menggunakan website IDX. Teknik pengambilan sampel menggunakan purposive sampling dengan metode analisis Independent Sample T-test. Hasil penelitian ini adalah 1) terdapat perbedaan antara pergerakan IHSG dan JII sebelum pandemi Covid-19, 2) terdapat perbedaan antara pergerakan IHSG dan JII saat terjadi pandemic Covid-19, 3) terdapat perbedaan antara pergerakan IHSG dan JII setelah new normal. Dengan demikian bahwa terdapat perbedaan yang signifikan antara pergerakan IHSG dan JII akibat dampak pandemic Covid-19.Kata Kunci: Keputusan Investasi Saham, Indeks Harga Saham, Pergerakan Harga Saham